Principles of Cystinosis Transition in Children - Saffari, Fatemeh; Arad, Banafshe (Journal of Pediatric Nephrology, 2020)
Children with chronic illness need special care during the transition to adolescence and adulthood. Cystinosis is a chronic childhood disease characterized by chronic renal failure and multi-organ involvement. With advances in treatment and kidney transplantation methods, the life expectancy of these patients has been prolonged. Renal transplantation is performed for most of the patients in childhood. These patients are at risk of non-adherence due to multiple drug usage and their chronic disease. As a child enters adulthood, parental care decreases and the patient should learn self-management. So the likelihood of non-compliance and loss of kidney transplant is high in transition time. This article gives a brief overview on transition of cystinosis patients from childhood to adolescence and adulthood